Cost of Producing Processed Oranges in Southwest Florida in 2017/18 - Ariel Singerman (EDIS)
This 4-page fact sheet written by Ariel Singerman and published by the UF/IFAS Food and Resource Economics Department presents a summary of the 2017/18 costs of production for processed oranges grown in southwest Florida. Typical users of these estimates include growers and consultants, who use them as a benchmark; property appraisers, who use them to compute the taxes for property owners; and researchers, who use the estimates to evaluate the economic feasibility of potential new technologies. http://edis.ifas.ufl.edu/fe1056